PERBEDAAN PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH ANTARA SISWA YANG DIBERI PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK DENGAN PENDEKATAN INKUIRI DI SMP NEGERI 2 TANJUNG MORAWA - Antonius KAP Simbolon; Hotmaida Sinaga (JURNAL CURERE, 2019)
The objectives of this study were to discover: (1) the differences of problem solving ability enhancement between students taught by applying realistic mathematical learning approach and Inquiry approach, (2) the interaction between learning approach (PMR and Inquiry) with the capability of beginning math students towards students’ problem solving ability enhancement, (3) the troubleshooting process of students’ problem solving between students taught by applying realistic mathematical learning approach and Inquiry approach. This study is a quasi experiment research. The population of this study consist of all students in grade VIII SMP Negeri 2 Tanjung Morawa. The sample of this study was 2 classes consist of 66 sudents taken by using cluster random sampling technique. The data was analyzed by using anova two lanes. It is found that (1) there is a difference of students problem solving enhancement between students taught by applying realistic mathematical learning approach and Inquiry approach, (2) there is an interaction between learning approach (PMR and Inquiry) with the capability of beginning math  students  towards  students’  problem  solving ability  enhancement, (3) a description discussion about the troubleshooting process of students problem solving students taught by applying realistic mathematical learning approach and Inquiry approach.